2010
DOI: 10.1523/jneurosci.2783-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Partial Deficiency or Short-Term Inhibition of 11β-Hydroxysteroid Dehydrogenase Type 1 Improves Cognitive Function in Aging Mice

Abstract: 11␤-Hydroxysteroid dehydrogenase type 1 (11␤-HSD1) regenerates active glucocorticoids (GCs) from intrinsically inert 11-keto substrates inside cells, including neurons, thus amplifying steroid action. Excess GC action exerts deleterious effects on the hippocampus and causes impaired spatial memory, a key feature of age-related cognitive dysfunction. Mice with complete deficiency of 11␤-HSD1 are protected from spatial memory impairments with aging. Here, we tested whether lifelong or short-term decreases in 11␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 37 publications
5
84
0
1
Order By: Relevance
“…Similar to other HSD1 inhibitors (Yeh et al, 2006), A-918446 and A-801195 robustly decrease cortisol formation in brain ex vivo tissue preparations. Although cognitive enhancement with HSD inhibitors in rodents has been shown after several days of treatment in older subjects (Sooy et al, 2010), these studies are the first to show that acute treatment with HSD1 inhibitors can improve cognitive performance. While young animals do not represent a model of AD, it is of interest to observe the glucocorticoid modulation can impact performance in otherwise healthy subjects.…”
Section: Discussionmentioning
confidence: 88%
“…Similar to other HSD1 inhibitors (Yeh et al, 2006), A-918446 and A-801195 robustly decrease cortisol formation in brain ex vivo tissue preparations. Although cognitive enhancement with HSD inhibitors in rodents has been shown after several days of treatment in older subjects (Sooy et al, 2010), these studies are the first to show that acute treatment with HSD1 inhibitors can improve cognitive performance. While young animals do not represent a model of AD, it is of interest to observe the glucocorticoid modulation can impact performance in otherwise healthy subjects.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, Holmes et al (2010) showed that an increased hippocampal expression of 11b-HSD1 was responsible for memory impairments in mice. Partial deficiency or short-term inhibition of 11b-HSD1 improves cognitive function in ageing mice (Sooy et al 2010). The fact that vitamin A deficiency induces anatomic and phenotypic changes comparable with those in neurodegeneration (Ghenimi et al 2009) could be partly linked to an increase in 11b-HSD1 expression at the central level.…”
Section: Discussionmentioning
confidence: 99%
“…In these tissues, increased local GC activation is postulated to contribute to the increased risk of fracture and osteoporosis and impaired cognitive function associated with aging. Improved cognition and increased long-term potentiation have been reported in aged 11β-HSD1 KO mice relative to age-matched controls (32), with improved memory consolidation, recall, and social recognition also reported following treatment with specific 11β-HSD1 inhibitors (33,34).…”
Section: Figurementioning
confidence: 91%